MATHEMATICS TEACHERS’ ANXIETY IN TEACHING AND LEARNING PROCESS: A LITERATURE REVIEW - Freddy Prasetyo; Suhendra Suhendra; Turmudi Turmudi (UNIVERSITAS MUHAMMADIYAH METRO, 2023)
Over the last few decades, many studies have placed attention on math anxiety in students, but math teachers can also experience anxiety that requires the attention. Math teachers can experience the anxiety in the form of math anxiety and math teaching anxiety, which can affect the learning process of mathematics. The purpose of this study is to identify the factors that cause math anxiety and math teaching anxiety in teachers. The method used in this research is Systematic Literature Review (SLR) with a survey-based descriptive approach through analysis the articles that fulfilled the inclution criteria, namely (1) published during the last ten years (2013-2022), (2) written in Indonesian or English, (3) indexed by Scopus or Sinta, which are browsed on the Google Scholar, ERIC, and Garuda database using the keywords “teachers’ math anxiety